Kerajaan Allah dalam Injil Markus - Siren Nugroho; Loria Loria; Delon Josephine Efrata; Sarmauli Sarmauli (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
In the historical and theological context, the Kingdom of God is understood not as a political or geographical kingdom, but as a spiritual reality present in human life and history. Through an analysis of Mark 1:15, this journal explains that the coming of Jesus signifies the fulfillment of God's plan of salvation and calls people to repent and believe in the gospel. This study also highlights Jesus' use of parables, such as the parable of the mustard seed and the growing seed, which illustrate the growth and characteristics of the Kingdom of God. By emphasizing the importance of repentance and faith, the results of the teachings indicate that the Kingdom of God is cultivating spiritual change in individuals. The conclusions obtained imply that although the Kingdom of God is already present, its full realization still awaits fulfillment in the future. Therefore, this paper recommends that Christians dig deeper into the concept of the Kingdom of God, improving their understanding and application of Kingdom values in daily life as a response to Jesus' teachings.